1996
DOI: 10.1557/jmr.1996.0185
|View full text |Cite
|
Sign up to set email alerts
|

Glass-ceramic sealants for solid oxide fuel cells: Part I. Physical properties

Abstract: A family of sealant materials has been developed for use in the solid oxide fuel cell (SOFC) and in other applications in the temperature range of 800-1000 ± C. These materials are based on glasses and glass-ceramics in the SrO-La 2 O 3 -Al 2 O 3 -B 2 O 3 -SiO 2 system. The coefficients of thermal expansion (CTE) for these materials are in the range of 8-13 3 10 26 ͞ ± C, a good match with those of the SOFC components. These sealant materials bond well with the ceramics of the SOFC and, more importantly, form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(105 citation statements)
references
References 4 publications
2
99
0
4
Order By: Relevance
“…Estes materiais devem possuir temperatura de transição vítrea mais baixa possível para evitar tensões devidas às diferenças de valores do coeficiente de expansão térmica [105]. Entretanto, a viscosidade destes materiais na temperatura de operação deve ser maior que 10 3 Pa.s para permanecerem estanques [105].…”
Section: Interconectores E Selantesunclassified
See 2 more Smart Citations
“…Estes materiais devem possuir temperatura de transição vítrea mais baixa possível para evitar tensões devidas às diferenças de valores do coeficiente de expansão térmica [105]. Entretanto, a viscosidade destes materiais na temperatura de operação deve ser maior que 10 3 Pa.s para permanecerem estanques [105].…”
Section: Interconectores E Selantesunclassified
“…Estes materiais devem possuir temperatura de transição vítrea mais baixa possível para evitar tensões devidas às diferenças de valores do coeficiente de expansão térmica [105]. Entretanto, a viscosidade destes materiais na temperatura de operação deve ser maior que 10 3 Pa.s para permanecerem estanques [105]. Os materiais comumente citados são à base de vidros sodacálcia, de outros silicatos alcalinos, de silicatos alcalinos terrosos e de borosilicatos alcalinos [105].…”
Section: Interconectores E Selantesunclassified
See 1 more Smart Citation
“…700900°C). In our previous work, 43) we reported that the GC9 glass and GC9 glass-ceramic with La/Ca ratio of 0.833 exhibited an excellent matching with the typical stainless steel interconnect and PEN plate at temperature below 650°C. Figure 2 shows the typical thermal expansion curves of GC9 glass with various La/Ca ratios in the range of 0 to 1.4.…”
Section: )50)mentioning
confidence: 83%
“…Sohn et al 19) found that the 42) have studied the Sr/Ca ratios on the structure, crystallization behavior and properties of diopside-based glass, and they reported that the tendency towards crystallization was retarded with increasing Sr/Ca ratio. Ley et al 43) found that the viscosity is sensitive to the B 2 O 3 /SiO 2 ratio in the SrOLa 2 Notably, a suitable glass-ceramic sealant for SOFC must offer a good wetting and mechanical strength to keep adhesion and gas tightness during operating at elevated temperatures. A novel barium-aluminum-borosilicate system glass named GC9, which was developed by the Institute of Nuclear Energy Research (INER) as a high-temperature seals for SOFC sealing.…”
Section: ¹6mentioning
confidence: 99%